Frontispiece: Improved Infrared Spectra Prediction by DFT from a New Experimental Database. Issue 35 (22nd June 2017) - Katari, Madanakrishna; Nicol, Edith; Steinmetz, Vincent; van der Rest, Guillaume; Carmichael, Duncan; Frison, Gilles
Abstract : Prediction of gas phase infrared spectra can be improved by correcting DFT results by using a linear function instead of a scaling factor, as has been demonstrated through an approach combining organometallic synthesis, mass spectrometry, IRMPD spectroscopy, and quantum chemical calculations. The experimental studies have provided a new data set which is used to benchmark DFT methods. A means of defining confidence limits for any given computed structure is provided, for more details see the Full Paper by G. Frison et al. onpage 8414 ff.